Optimizing Rail System Stability: Investigating Wear Patterns in Adjustable Steel Washer Equipped Base Plate Designs - Goh, Ching Pang; Tan, Weng Chun (INTI International University, 2023)
The rail fastening system is a critical component ensuring the secure attachment of rails, thereby playing a pivotal role in track safety and the prevention of derailments. Key constituents, including rail clamps, tensioning bolts, washers, elastomer pads, and base plates, collectively contribute to the system's efficacy. In the context of Malaysia, the base plate design has remained unchanged for more than a decade. Notably, the adjustable washer, crucial for absorbing train vibrations, encounters compatibility issues with the teeth configuration of the base plate. Consequently, excessive rotational force is necessitated during installation, resulting in initial deformation and wear. This adversely affects the performance of both the base plate and the rail fastening system. To address these challenges, this research undertakes a comprehensive investigation and analysis aimed at enhancing the performance and design of the base plate and its associated components. The outcomes reveal a redesigned base plate capable of reducing stress on the tooth structure by an impressive 69.4%.